2019
DOI: 10.1021/acs.jpclett.9b02383
|View full text |Cite
|
Sign up to set email alerts
|

Predictions on High-Power Trivalent Metal Pentazolate Salts

Abstract: High-energy-density materials (HEDMs) have been intensively studied for their significance in fundamental sciences and practical applications. Here, using the molecular crystal structure search method based on first-principles calculations, we have predicted a series of metastable energetic trivalent metal pentazolate salts MN15 (M= Al, Ga, Sc, and Y). These compounds have high energy densities, with the highest nitrogen content among the studied nitrides so far. Pentazolate N5 – molecules stack up face-to-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 78 publications
1
53
1
Order By: Relevance
“…[ 104,105 ] Three possible bonding modes were proposed, i.e., monodentate, bidentate, and metallocene‐like coordination. Recent first‐principles calculations combined with modern structure search algorithms have predicted a rich variety of crystal structures, such as in MN 5 (M = H, Na, and Cu), [ 30,34,106 ] MN 10 (M = Be, Ca, Mg, Ba, and Zn), [ 33,107–109 ] MN 15 (M = Al, Ga, Sc, and Y), [ 110 ] and IrN x ( x = 4, 7), [ 111 ] and estimated the synthesis conditions and energetic performance for many. These studies are critical, as they often serve to guide the experimental exploration of new materials, such as in the case of LiN 5 and CsN 5 .…”
Section: Nitrogen‐rich Compoundsmentioning
confidence: 99%
“…[ 104,105 ] Three possible bonding modes were proposed, i.e., monodentate, bidentate, and metallocene‐like coordination. Recent first‐principles calculations combined with modern structure search algorithms have predicted a rich variety of crystal structures, such as in MN 5 (M = H, Na, and Cu), [ 30,34,106 ] MN 10 (M = Be, Ca, Mg, Ba, and Zn), [ 33,107–109 ] MN 15 (M = Al, Ga, Sc, and Y), [ 110 ] and IrN x ( x = 4, 7), [ 111 ] and estimated the synthesis conditions and energetic performance for many. These studies are critical, as they often serve to guide the experimental exploration of new materials, such as in the case of LiN 5 and CsN 5 .…”
Section: Nitrogen‐rich Compoundsmentioning
confidence: 99%
“…10 Various metal pentazolates ( pentazolates of Na, K, Rb, Be, Mg, Ba, Al, Ga, Sc, Y, and Zn) have been recently predicted using modern structure search algorithms, but have not yet been discovered experimentally. [11][12][13][14][15][16][17][18] Here we studied the reactions between NaN 3 and nitrogen in laser-heated diamond anvil cells attempting to extend the series of water and oxygen-free alkali-metal pentazolates. Surprisingly, in addition to the expected simple sodium pentazolate salt NaN 5 , we have also synthesized a never predicted complex pentazolate framework structure with incorporated dinitrogen molecules (NaN 5 •N 2 ) and the sodium-rich pentazolate Na 2 N 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, we have found that metal nitrides have attracted more and more attention. 50,51 Because metal nitrides are more stable than pure nitrogen compounds in terms of kinetics, and have the characteristics of low synthesis pressure and superior physical and chemical properties, they can be widely used in the research of high energy-density materials. 3 3.1 CaN 6 with P 1 structure…”
Section: Resultsmentioning
confidence: 99%